Going against the grain: a case report of an endometriosis in the canal of Nuck - Karam Karam; Lamia Azizi; Mehsen Azizi; Emile Dabaj (European Journal of Case Reports in Internal Medicine)
The canal of Nuck is an embryological remnant of the processus vaginalis found in females, and is a potential site for endometriosis seeding. Endometriosis in the canal of Nuck is an exceedingly rare condition. Patients with this condition present with groin swelling or suprapubic pain. We describe a case of a 44-year-old female presenting for left inguinal pain and a lump. Physical examination revealed a 3 cm reducible mass; magnetic resonance imaging (MRI) revealed a 6.2 × 3.0 × 1.7 cm multiloculated cystic structure, extending from the left pelvic region into the left inguinal region near the round ligament. The patient underwent surgical excision of the mass. Pathology revealed a multi-cystic lesion lined with mesothelium cells and a fibrous wall with multiple foci of misplaced endometrial glands and stroma, corroborating a diagnosis of endometriosis in the canal of Nuck.